Pediatric Epilepsy Surgery in A Drug-Resistant Epilepsy Patient Aggravated by SARS-CoV-2: A Case Report - Edeline Samudra; Retno Jayantri Ketaren; Made Agus Mahendra Inggas (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2025)
Introduction: Epilepsy is a manageable neurological disorder, but about one-third of cases are classified as drug-resistant epilepsy (DRE). DRE in pediatrics is more complex and may lead to cognitive function impairment, while surgery can offer seizure control in cases of focal DRE. Case: A 10-year-old male presented with a four-year history of recurrent seizures, thought to be caused by a left temporal cerebral cyst diagnosed five years earlier. During episodes, he experienced body stiffness, bilateral eye twitching, and drooling, with intact consciousness. After SARS-CoV-2 exposure, seizures became more frequent despite antiepileptic treatment, leading to partial resection of the left temporal lobe nine months later. Two years post epileptic surgery, he has become drug-responsive and achieved seizure control with symptomatic relief through medication. Discussion: Epilepsy is common in children, and DRE should be considered in cases of intractable epilepsy. Various factors can cause DRE, and in this patient, SARS-CoV-2 is thought to aggravate seizures by binding to ACE2 receptors in the central nervous system. This neural interaction may trigger reactive astrogliosis and neuroinflammation, disrupting the balance between glutamate and GABA levels. However, epilepsy surgery has been effective in improving the quality of life. Conclusion: Epilepsy surgery, either resective or non-resective surgery, is still rarely performed in Indonesia, while the management of DRE may require surgery. Although complete seizure freedom is not guaranteed, surgery can often convert DRE into a drug-responsive condition.